Accuracy and precision of flash glucose monitoring sensors inserted into the abdomen and upper thigh compared with the upper arm. Issue 6 (27th February 2018) - Charleer, Sara; Mathieu, Chantal; Nobels, Frank; Gillard, Pieter
Abstract : Nowadays, most Belgian patients with type 1 diabetes use flash glucose monitoring (FreeStyle Libre [FSL]; Abbott Diabetes Care, Alameda, California) to check their glucose values, but some patients find the sensor on the upper arm too visible. The aim of the present study was to compare the accuracy and precision of FSL sensors when placed on different sites. A total of 23 adults with type 1 diabetes used three FSL sensors simultaneously for 14 days on the upper arm, abdomen and upper thigh. FSL measurements were compared with capillary blood glucose (BG) measurements obtained with a built‐in FSL BG meter. The aggregated mean absolute relative difference was 11.8 ± 12.0%, 18.5 ± 18.4% and 12.3 ± 13.8% for the arm, abdomen ( P = .002 vs arm) and thigh ( P  = .5 vs arm), respectively. Results of Clarke error grid analysis for the arm and thigh were similar (zone A: 84.9% vs 84.5%; P  = .6), while less accuracy was seen for the abdomen (zone A: 69.4%; P  = .01). Apart from the first day, the accuracy of FSL sensors on the arm and thigh was more stable across the 14‐day wear duration than accuracy of sensors on the abdomen, which deteriorated mainly during week 2 ( P  < .0005). The aggregated precision absolute relative difference was markedly lower for the arm/thigh (10.9 ± 11.9%) compared with the arm/abdomen (20.9 ± 22.8%; P  = .002). Our results indicate that the accuracy and precision of FSL sensors placed on the upper thigh are similar to the upper arm, whereas the abdomen performed unacceptably poorly.